Female Empowerment and Male Backlash - Eleonora Guarnieri; Helmut Rainer (Center for Economic Studies and ifo Institute (CESifo), 2018)
Do policies and institutions that promote women's economic empowerment have a long-term impact on intimate partner violence? We address this question by exploiting a natural experiment of history in Cameroon. From the end of WWI until 1961, the western territories of today's Cameroon were arbitrarily divided between France and the United Kingdom, whose colonial regimes opened up divergent economic opportunities for women in an otherwise cul- turally and geographically homogeneous setting. Women in British territories benefited from a universal education system and gained opportunities for paid employment. The French colonial practice in these domains centered around educating a small administrative elite and investing in the male employment-dominated infrastructure sector. Using a geographical regression discontinuity design, we show that women in former British territories are 30% more likely to be victims of domestic violence than those in former French territories. Among a broad set of possible channels of persistence, only one turns out statistically significant and quantitatively important: women in former British territories are 30% more likely to be in paid employment than their counterparts in former French areas. These results are incompatible with household bargaining models that incorporate domestic violence but they are accommodated by theories of male backlash.
Keywords: J12; J16; N37; Z13; 330; colonization; female economic empowerment; intimate partner violence